2004
DOI: 10.1161/01.atv.0000139011.94634.9d
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Regulation of Vascular NAD(P)H Oxidase Activity and Nox Isoform Expression in Human Arteries and Veins

Abstract: Objective-Impaired endothelial function, characterized by nitric oxide scavenging by increased superoxide production, is a hallmark of vascular disease states. However, molecular mechanisms regulating superoxide production in human blood vessels remain poorly defined. Methods and Results-We compared endothelial function, vascular superoxide production, and the expression of NAD(P)H oxidase subunits in arteries and veins from patients undergoing coronary bypass surgery (nϭ86). Superoxide release was similar in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 41 publications
(45 reference statements)
7
85
0
1
Order By: Relevance
“…The NADPH oxidase system is regulated systemically in veins and arteries, which strengthens the importance of the molecular regulation of the enzyme in CVD (11).…”
mentioning
confidence: 66%
“…The NADPH oxidase system is regulated systemically in veins and arteries, which strengthens the importance of the molecular regulation of the enzyme in CVD (11).…”
mentioning
confidence: 66%
“…Studies in adiponectin knockout mice (7) have shown increased NADPH oxidase activity in these animals. Given that type 2 diabetes is associated with increased activity of NADPH oxidase in experimental models (28,29) and the vascular wall (26,30), hypoadiponectinemia (a key feature in obesity and type 2 diabetes) (7) might be a link between type 2 diabetes and vascular disease pathogenesis. At a clinical level, adiponectin released by PVAT exerts vasodilatory effects on human microvessels (31), while weight loss leading to increased adiponectin levels at the same time improves endothelial function and reduces serum NOX2 levels (32).…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of Noxs in human vessels has focused mainly on discarded surgical tissue from patients undergoing bypass surgery. Results from extensive human studies by the Channon group showed increased vascular Nox activity and expression of Nox2, Nox4, and p22phox, but not of Nox1, in patients with coronary artery disease or diabetes (10, [76][77][78]. Others showed that vascular Nox5 expression is increased in patients with atherosclerosis and cardiac disease (18, 178,195).…”
Section: Ros and Noxs In Human Vesselsmentioning
confidence: 99%